Uso de assembléia de peixes para desenvolvimento de um índice de integridade biótica (IBI) padrão em diferentes ecossistemas - Pesoa, Nicolle Albornoz (Universidade do Vale do Rio dos Sinos, 2011)
Population growth has led to an increased use of natural resources. In Brazil, the threats to water systems are mostly caused by the use of water in agriculture and irrigation, leading to environmental, and, thus, biota changes. Studies on the Index of Biotic Integrity (IBI) using fish communities have helped clarify the status of the quality of water resources. The Index of Biotic Integrity (IBI), defined by KARR as an integrator of ecological and environmental factors has been successfully used to assess the size of the disruption in the environment, and in subsequent studies the IBI was adapted to fish communities in very different environments, such as lakes, estuaries and reefs. The studies conducted so far using protocols for IBI have usually assessed sections of a river or very different sites, and the metrics are adapted according to the case. In the present study, 27 points sampled for the knowledge of the structure of the fish community and the species occurring there were assessed, and a standard IBI was adapted with the purpose of assessing different sites. 62,141 individuals of 95 species were recorded, with Hyphessbrycon luetkenii being the most abundant species. At first, 19 metrics were suggested, which have undergone a process of selection and evaluation of sensitiveness. A standard protocol of eight final metrics for inclusion in the Index of Biotic Integrity was then generated.
Keywords: Índice de integridade biótica; Peixes; Recursos hídricos; ACCNPQ::Ciências Biológicas::Biologia Geral